2015
DOI: 10.1016/j.anplas.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance et changement des implants mammaires en gel de silicone : étude rétrospective a propos de 130cas de rupture d’implants

Abstract: The results suggest that implant ruptures of silicone gel breast implants are under diagnosed. Clinical follow-up seems insufficient to diagnose implant ruptures. Ultra sound surveillance (± MRI) could be proposed 4 years, 7 years and 10 years after the initial surgery. It does not seem appropriate to propose a systematic change of implant without the incidence of a rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The average time from implantation to detection of rupture was 9.2 years. 42 Implant rupture can be either intracapsular when is confined to the fibrous capsule, or extracapsular when extravasation of implant contents extends outside the capsule into fibroadipose tissue, skeletal muscle or breast parenchyma.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The average time from implantation to detection of rupture was 9.2 years. 42 Implant rupture can be either intracapsular when is confined to the fibrous capsule, or extracapsular when extravasation of implant contents extends outside the capsule into fibroadipose tissue, skeletal muscle or breast parenchyma.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The incidence of implant rupture is 1% to 8% 34 . In a multi-institutional study involving 130 patients with ruptured implants, Pineau et al 42 found that only 20% of patients with ruptured implants complained of an abnormality; 60% of implant ruptures were discovered during screening for breast cancer and 20% were discovered incidentally during preoperative examination for cosmetic surgery. The average time from implantation to detection of rupture was 9.2 years 42 .…”
Section: Ruptured Implantmentioning
confidence: 99%
See 1 more Smart Citation